Pengaruh Beban Kerja Dan Budaya Organisasi Terhadap Employee Engagement Pada Nam Air Di Jakarta - Lestari, Agung Tri; Rofiyanti, Eka; Wulandari, Winda Wulandari (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to determine and analyze the influence of workload and organizational culture on employee engagement at NAM Air in Jakarta. This is motivated by the problem that many pilots choose to change jobs. Furthermore, there are also problems with pilot flying hours and working hours which are only valid for two months. This research was conducted at NAM Air in Jakarta from April to August 2021. This study used a quantitative approach. Data was collected by distributing questionnaires to 44 respondents. This study shows that there is a significant influence between the workload variable on the employee engagement variable, which is 24.5%, there is a significant influence between the organizational culture variable on the employee engagement variable, which is 21.4%, and there is a positive and significant effect on workload and culture. organization simultaneously on employee engagement pilot PT. NAM Air is 32.3%